Towards equal justice: Addressing the disparity in victim compensation across Indian states - Ipsita Ojal; Varinder Kaur (Social Sciences and Humanities Open)
Victim compensation in India varies significantly across different states, resulting in a glaring disparity that raises concerns about fairness and equality. The current system, which allows each state to set its own compensation guidelines, often leaves victims in certain regions inadequately compensated compared to others. This inconsistency contradicts the fundamental principle that all victims, irrespective of their location, deserve equal and sufficient financial support to rebuild their lives after suffering from heinous crimes such as acid attacks, domestic violence, or other traumatic incidents. When compensation policies are inconsistent, victims from states with lower payouts face additional hardships, further exacerbating their suffering. Such disparities not only undermine the spirit of justice but also highlight the lack of a standardized approach to victim welfare across the country. There is an urgent need to establish a uniform, nationwide compensation framework that ensures all victims receive adequate and fair support, regardless of where they reside. By advocating for a more equitable system, we can ensure that every victim is treated with dignity and receives the assistance necessary to aid in their recovery, reflecting the true essence of justice and compassion.